Legal Aspects of Electronic Money: Financial Inclusion Instrument. The Peruvian Model - Cipriano Pirgo, Manuel (2015)
In the first part, the background of electronic money is explained, then it provides a detailed account of how it has evolved in Africa, where there has been a huge success, given the advantages and applications it has, and how it has been working. Elsewhere, other models of electronic money that are emerging in the world, such as Google Wallet, Apple Pay, and experiences in Peru as Wanda and Your Mobile Money.In the third part, some aspects of the recent regulation of electronic money in Peru are required by Act No. 29985, which regulates the basic characteristics of electronic money. Finally, it details the recent proposal that ASBANC has been working on through the Model Peru, as well as technological and regulatory risks that still must be faced.